GAMBARAN PENGETAHUAN DAN SIKAP SISWA TENTANG KESIAPSIAGAAN MENGHADAPI GEMPA BUMI DI SMAN 3 PAINAN TAHUN 2022 - Zeswita, Armein Lusi; Indriati, Gustina; Sitepu, Nurlaila (Ensiklopedia of Journal, 2023)
West Sumatra is an area that often experiences earthquakes and one of them is the South Coast which often experiences earthquakes and West Sumatra is a red zone which is prone to earthquakes. Children are part of a community that is vulnerable to earthquake hazards. The large number of losses and victims is caused by a lack of awareness and knowledge about disasters, both the vulnerability of the area of residence and the lack of knowledge about rescue actions when a disaster occurs. This study aims to determine the knowledge and attitudes of SMAN 3 Painan students regarding earthquake preparedness. SMAN 3 Painan is 700 meters from the beach and this school is a boarding school for students. The design of this research is descriptive quantitative, and conduct research at SMAN 3 Painan in 2022. The number of students is 219 people and the respondents for the research are SMAN 3 Painan students, totaling 141 people and the sampling technique is using random sampling. The research measuring tool is using a questionnaire and data analysis with univariate analysis. Based on the results of the study it was found that students who had good knowledge were 101 people (71.6%) and had sufficient knowledge as many as 24 people (17%) and 16 people (11.3%) had less knowledge. For the assessment of student attitudes, it was found that 49 students (34.8%) had sufficient attitudes. It is suggested to the school related to earthquake preparedness and find out about evacuation routes and know the assembly points in the event of an earthquake.